Kinetic evidence for the formation of monocationic N,N'-Disubstituted Phthalamide in tertiary Amine-Catalyzed hydrolysis of N-Substituted Phthalimides - Ariffin, Azhar; Khan, M.N.; Sim, Y.L. (2007)
A kinetic study on the aqueous cleavage of N-(2-methoxyphenyl)phthalimide (1) and N-(2-hydroxyphenyl)-phthalimide (2), under the buffers of N-methylmorphohne, reveals the equilibrium presence of monocationic amide (Ctam) formed due to nucleophilic reactions of N-methylmorpholine with 1 and 2. Pseudo-first-order rate constants for the reactions of water and HO- with Ctam (formed through nucleophilic reaction of N-methylmorpholine with 1) are 4.60 x 10(-5) s(-1) and 47.9 M-1 s(-1), respectively. But the cleavage of Ctam, formed through nucleophilic reaction of N-methylmorpholine with 2, involves intramolecular general base (2(')-0(-) group of Ctam)-assisted water attack at carbonyl carbon of cationic amide group of Ctam in or before the rate-determining step.